Hydro-mechanical power split transmissions: Progress evolution and future trends. (February 2019) - Yu, Jin; Cao, Zhu; Cheng, Min; Pan, Rongzhao
The hydro-mechanical power split transmission is an important form of hydraulic hybrid transmission, combining the stepless speed characteristics of hydraulic transmission and the high efficiency of mechanical transmission. Recently, the hydro-mechanical power split transmission, with its relatively large potential for energy recovery and improving the environment, and its low cost, has attracted many scholars from all over the world. Because there are many types of hydro-mechanical power split transmission, the different forms are complex, and researchers across the world are relatively dispersed, it has experienced a long and arduous development process. Therefore, it is important to summarize the types, developments, and achievements of this transmission. From the recent literature at home and abroad, this paper summarizes developments, key techniques and trends, analyses problems and difficulties in design and application, discusses the methods for solving these problems, and provides references for the development and application of hydro-mechanical power split transmission.